Living with our buildings and infrastructure: adapting for the future. ARCC network research update 2012 - Street, R (Adaptation and Resilience to a Changing Climate Coordination Network, 2012)
The performance of UK buildings and infrastructure systems at both the national and local level is critical to our national health, well-being and economic stability. Yet these sectors face serious challenges over the next 20–50 years and beyond if they are to remain resilient to the impacts of future climate change and capable of responding to expected demographic, social and economic trends. Given the long lifetimes of many buildings (domestic and nondomestic) and infrastructure systems (water, energy, waste, telecommunications and transport), informed decisions need to be taken now to ensure resilient and sustained performance in the face of on-going changes in our climate. The country is now experiencing higher temperatures, changing rainfall patterns and more extreme weather events such as floods, heatwaves and droughts. Our existing buildings and infrastructure are already struggling to cope at times and these changing weather conditions are likely to become more pronounced into the future. This brochure summarises research findings and outputs to date from projects within the ARCC CN and highlights the implications for end users. Further information can be found in the links and references given in each project summary or on the ARCC CN website.